Understanding the socio-economic causes of deforestation: a global perspective - Prochazka, Petr; Abrham, Josef; Cerveny, Jaroslav; Kobera, Lukas; Sanova, Petra; Benes, Daniel; Fink, Julia-Maria; Jiraskova, Eliska; Primasova, Simona; Soukupova, Jana; Smutka, Lubos (Frontiers in Forests and Global Change, 2023)
Introduction This paper investigates the links between deforestation and key economic, social, environmental, and geographical variables. We focus on per capita GDP, total forest cover, and the population across a diverse sample of countries from five continents for the last three decades. Methods This study utilizes a regression model using panel data to show the impact of key economic, and social variables on deforestation. Also, set of dummy variables is introduced in the paper. To enable the investigation, we use a set of dummies to capture their influence. The random effect specifications are used in this investigation. The research focuses on a period ranging from 1990 to 2020. Results Results show how different socio-economic variables influence deforestation. For example, disruptive events like the COVID-19 pandemic and the financial crisis had a negative effect on forest area development across all models. GDP per capita has different impact depending on the size of a country. Former colonies seem to have more deforestation. Conclusions The global environmental challenges posed by human activities and their impact on the state of forest have become increasingly evident. It is necessary to undertake policy and governance reforms to establish a solid legal framework, strengthen enforcement mechanisms, and foster transparency and accountability. The promotion of sustainable agriculture and agroforestry practices can substantially alleviate pressure on forests. Furthermore, it is necessary to mitigate disruptive events like pandemics by establishing specific strategies and creating contingency plans.